Badania polskiej leksyki zmysłowej na podstawie tekstów literackich = Research on Polish sensory Lewis on the basis of literary texts - Kładoczny, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The lexis describing sensory experiences, regardless of how many times it has been described before, is still an interesting field of research due to its historical, idiolectal and sociolinguistic aspects. Literary texts should be regarded as suitable for this type of analysis and interpretation, not only owing to their self-contained nature, but more importantly, due to their qualitative values, including in particular, a variety of vocabulary.
Keywords: konceptualizacja; zmysły; utrata wzroku; hierarchia zmysłów; rama semantyczna; conceptualization; senses; loss of sight; hierarchy of senses; semantic frame